Does fair coach behavior predict the quality of athlete leadership among Belgian volleyball and basketball players: the vital role of team identification and task cohesion - De Backer, M.; Van Puyenbroeck, S.; Fransen, K.; Reynders, B.; Boen, F.; Malisse, F.; Vande Broek, G. (Frontiers in Psychology, 2021)
A vast stream of empirical work has revealed that coach and athlete leadership are important determinants of sport teams` functioning and performance. Although coaches have a direct impact on individual and team outcomes, they should also strive to stimulate athletes to take up leadership roles in a qualitative manner. Yet, the relation between coach leadership behavior and the extent of high-quality athlete leadership within teams remains underexposed. Based on organizational justice theory and the social identity approach, the present research tested whether perceived justice of the coach positively predicts the quality of athlete leadership. Furthermore, we examined the role of group dynamic processes (i.e., team identification and task cohesion) within this relation. Belgian volleyball (N = 161) and basketball players (N = 78) were asked to rate the justice of their coach, their team identification, the task cohesion, and the athlete leadership quality in the team. Structural equation modeling indicated that coaches` perceived justice positively predicted the quality of athletes` leadership, and that this relation was established through three intermediate steps (i.e., from team identification to task cohesion, to athlete leadership quality). These results suggest that fair coach behavior does not only bridge the gap between leadership and followership, it also has the potential to improve the quality of athletes` leadership within sport teams. More specifically, findings suggest that coaches` perceived justice cultivates a shared social identity characterized by high levels of players` identification with their team, which in turn increased their perceptions of the team`s task cohesion. Finally, this increased task cohesion encouraged the athlete leaders to demonstrate high-quality leadership.